Lyoathelia tsugae sp. nov. (Agaricomycetes), a new corticioid wood-decaying fungus associated with Tsuga tchekiangensis in subtropical China - Li, Ming-Rui; Zhao, Ya-Lin; Zeng, Gunag-Yu; Zhaung, Lei; Dai, Yu-Cheng (Phytotaxa, 2026)
Tsuga tchekiangensis is a rare coniferous tree in southern China, with a limited distribution in very high mountains in subtropical China. Knowledge of wood-decaying fungi on T. tchekiangensis was limited previously, and two samples of a white corticioid fungus on rotten wood of T. tchekiangensis were collected during a field trip. After morphological examination and phylogenetic analysis, it turned out that these samples represented a new species, Lyoathelia, viz. L. tsugae. The new taxon is characterized by annual, resupinate basidomata with white rhizomorphs at the margin and inside substrate, a white and smooth monomitic hyphal system with clamp connections on generative hyphae, the presence of clavate cystidia, globose basidiospores measuring 5.5–6.3 × 5.3–6 µm, growing on rotten wood of Tsuga tchekiangensis. Lyoathelia laxa is phylogenetically and morphologically closely related to L. tsugae, but the former has bigger basidiospores (6–8 × 5.5–6.5 µm). A description, illustrations, and phylogenetic analysis results for the new species are provided, with comparisons to the closely related taxa.